Tissue stiffness heterogeneity in the jaw and temporomandibular joint: its impact on tumor metabolism and considerations for in vitro model development - Li, Lingjie; Deng, Ping; Hou, Siyu; Li, Guangyue; Suo, Min; Xu, Ling; Wang, Chao; Song, Jinlin (Frontiers in Physiology, 2025)
Malignant bone- and cartilage-forming tumors exhibit heterogeneous clinical behavior across various body regions. Understanding the mechanisms underlying these differences is essential for developing targeted diagnostic and therapeutic strategies. This review proposes the hypothesis that tissue stiffness heterogeneity contributes to the distinct progression and prognosis of tumors in the jaw and temporomandibular joint (TMJ) compared to peripheral skeletal sites, potentially through stiffness-mediated metabolic reprogramming. To evaluate this hypothesis, a conceptual framework is provided to guide future research. This review summarizes spatial and temporal variations in stiffness across the jaw, TMJ, and femur, and introduces potential mechanisms through which mechanical stiffness may influence tumor metabolism. Technical strategies and material considerations for designing scaffolds that mimic bone and cartilage stiffness are discussed, along with current applications of stiffness-biomimetic scaffolds for in vitro investigation of malignant bone- and cartilage-forming tumors. By integrating insights from mechanobiology, tumor metabolism, and scaffold engineering, this review aims to facilitate the development of targeted experimental approaches that may contribute to more effective treatment strategies.